Cardiothoracic surgery leadership and learning are indispensable to each other. Issue 12 (8th November 2022) - Bashir, Mohamad; Jubouri, Matti; Chen, Edward P.; Mariscalco, Giovanni; Narayan, Pradeep; Bailey, Damian M.; Awad, Wael I.; Williams, Ian M.; Velayudhan, Bashi; Mohammed, Idhrees
Abstract: Cardiothoracic surgery is facing a multitude of challenges in leadership and training on the global scale, these being a complex and aging patient population, shortage of cardiac surgeons, diminishing student interest and trainee enthusiasm, increasingly challenging training obstacles and work‐life imbalances, suboptimal job prospects, reports of discrimination and bullying and lack of diversity as well as gap between innovation and technology, clinical application, and training of future surgeons. The survival of cardiac surgery hinges on the leadership attracting and retaining young surgeons into the specialty. Mentoring, leading through example, recognizing the work‐life imbalances, adapting to diverse and modern training models and embracing diversity with respect to gender and race, will ultimately be required to create and cultivate a nurturing environment of training and preparing future leaders. The vision for training future generations of cardiothoracic surgeons must rely heavily on strengthening the unity of the heart team. In doing so we can provide the best possible care for our patients and a most fulfilling career for the future generation of cardiac surgeons.